Successful Continuous Adductor Canal Block Placement in a Patient With Absent Sartorius Muscle: A Case Report. Issue 4 (15th August 2017) - Lin, Shin-E; Auyong, David B.; Dahl, Aaron B.; Hanson, Neil A.
Abstract : We report a novel case of a patient who presented for elective total knee arthroplasty and had distorted adductor canal anatomy due to previous sartorius rotational flap surgery. Despite the lack of a sartorius muscle on the intended operative limb, we describe the successful placement of a continuous adductor canal block. This case is a clinically relevant example that highlights the importance of the vastoadductor membrane as the anatomical anteromedial boundary for the adductor canal, and that it remains intact even after sartorius muscle flap surgery. Abstract : Supplemental Digital Content is available in the text.